"The things that people can't see" The impact of TBI on relationships: an interpretative phenomenological analysis. (20th March 2020) - O'Keeffe, Fiadhnait; Dunne, Johann; Nolan, Maeve; Cogley, Clodagh; Davenport, John
ABSTRACT: Objective : To explore the impact of TBI on couple relationships, from the perspective of both injured and uninjured partners in the relationship. Method : In-depth, semi-structured interviews were conducted with six uninjured women and five of their male partners living with TBI for between four and eight years who had attended a tertiary neurorehabilitation service. The principles of Interpretative Phenomenological Analysis (IPA) were used to analyze the data. Results : The three major themes emerged. Broken Bonds: "those special things just between the two of us" captures the emotional fallout from TBI on each individual and on the relationship; New Dynamics: "like oil and water" describes the effect of individual changes on relationship dynamics in general, on sexuality, conflict and family life; Moving Forward Together: "We figure it out" describes coping strategies in maintaining relationships post-TBI including hope, time, understanding TBI and positive reappraisal. Conclusions : This research provides an in-depth, phenomenological account of couples' experiences of the impact of TBI on relationships, including the perspectives of both TBI survivors and their partners. The three major themes that emerged capture the stresses that impinge on relationships post-TBI and confirms the importance of supportive clinical interventions for couples as an essential component of neurorehabilitation.